Pentingnya Pendidikan Karakter untuk Peserta Didik SD Ditengah Perkembangan Teknologi - Keyzia Dwi Riyani; Adrias Adrias; Aissy Putri Zulkarnaini (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The development of digital technology has brought significant changes in various aspects of life, including education. Elementary school children are now growing up in a digital era full of challenges, both in terms of easy access to information and negative impacts such as gadget addiction and decreased social interactions. Character education plays a key role in shaping children's morals, ethics, and responsibility in utilizing technology wisely. This article discusses the urgency of character education, the impact of technology on children's development, and strategies for implementing character education in the digital era.